Employment effects of payroll tax subsidies - Matthias Collischon; Kamila Cygan-Rehm; Regina T. Riphahn (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
This paper exploits several reforms of wage subsidies in the framework of the German Minijob program to investigate substitution and complementarity relationships between subsidized and non-subsidized labor demand. We apply an instrumental variables approach and use administrative data on German establishments for the period 1999-2014. Particularly in small establishments (0-9 employees), subsidized Minijob employment comprises large shares of the work force, on average over 40 percent. For these establishments, robust evidence shows that increasing the subsidization of Minijob employment crowds out non-subsidized employment. Our results imply that Minijob employment in 2014 may have eliminated more than 0.5 million unsubsidized employment relationships just in small establishments. This represents an unintended and harmful consequence of the Minijob subsidy.
Keywords: J21; J23; J38; C26; 330; wage subsidy; Minijob; labor demand; substitution effect; crowding out effect; displacement effect; employment; payroll tax